Cellular responses to modified Plasmodium falciparum MSP 119 antigens in individuals previously exposed to natural malaria infection (2009)
Background: MSP1 processing-inhibitory antibodies bind to epitopes on the 19 kDa C-terminal region of the Plasmodium falciparum merozoite surface protein 1 (MSP119), inhibiting erythrocyte invasion. Blocking antibodies also bind to this antigen but prevent inhibitory antibodies binding, allowing invasion to proceed. Recombinant MSP119 had been modified previously to allow inhibitory but not blocking antibodies to continue to bind. Immunization with these modified proteins, therefore, has the potential to induce more effective protective antibodies. However, it was unclear whether the modification of MSP119 would affect critical T-cell responses to epitopes in this antigen. Methods: The cellular responses to wild-type MSP119 and a panel of modified MSP119 antigens were measured using an in-vitro assay for two groups of individuals: the first were malaria-naïve and the second had been naturally exposed to Plasmodium falciparum infection. The cellular responses to the modified proteins were examined using cells from malaria-exposed infants and adults. Results: Interestingly, stimulation indices (SI) for responses induced by some of the modified proteins were at least two-fold higher than those elicited by the wild-type MSP119. A protein with four amino acid substitutions (Glu27→Tyr, Leu31→Arg, Tyr34→Ser and Glu43→Leu) had the highest stimulation index (SI up to 360) and induced large responses in 64% of the samples that had significant cellular responses to the modified proteins.